PENGUJIAN HARMONISA DAN UPAYA PENGURANGAN GANGGUAN HARMONISA PADA LAMPU HEMAT ENERGI - Liem Ek Bien, Liem Ek Bien; Sudarno, Sudarno (Jurnal Teknik Elektro, 2004)
Harmonic (current or voltage) is one of the problems that has to be solved in electric powersystem, especially that caused by non-linear loads. Harmonic could cause bad impacts forthe electric components that sensed it. It is almost certain that using of fluorescent lamp withelectronic ballast or it is called energy saving lamp can cause harmonic in electric powersystem. Considering of the using of energy saving lamp is increased fairly fast as residenceand office lighting, so it is important to analyze and solve the harmonic that caused byenergy saving lamp. From the harmonic analysis, we can know the harmonic distortioncaused by energy saving lamp. And there are some efforts to reduce such harmonicdistortion by using a simple harmonic filter.Keyword: power quality, harmonic, harmonic filter.